GeO2 glass ceramic planar waveguides fabricated by RF-sputtering - Chiasera, A. (2014)
GeO2 transparent glass ceramic planar waveguides were fabricated by a RF-sputtering technique and then irradiated by a pulsed CO2 laser. Different techniques like m-line, micro-Raman spectroscopy, atomic force microscopy, and positronbannihilation spectroscopy were employed to evaluate the effects of CO2 laser processing on the optical and structuralbproperties of the waveguides. The GeO2 planar waveguide after 2h of CO2 laser irradiation exhibits an increase of 0.04 inbthe refractive index, measured at 1542 nm. Moreover, the technique of laser annealing is demonstrated to significantlybreduce propagation loss in GeO2 planar waveguides due to the reduction of the scattering. Upon irradiation of the surfacebthe roughness decreases from 1.1 to 0.7 nm, as measured by AFM. Attenuation coefficients of 0.7 and 0.5 dB/cm at 1319 and 1542 nm, respectively, were measured after irradiation. Micro-Raman measurements evidence that the system embeds GeO2 nanocrystals and their phase varies with the irradiation time. Moreover, positron annihilation spectroscopy was used to study the depth profiling of the as prepared and laser annealed samples. The obtained results yielded information on the structural changes produced after the irradiation process inside the waveguiding films of approximately 1 μm thickness.